Modernizing the Curricula of Statistics Courses through Statistical Learning - Nunes, Marcus Alexandre (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
With recent advances in computer technology, it has become easier to fit complex models to data. Moreover, free computing cloud alternatives can help those without a powerful computer in this fashion. Nonetheless, many data repositories from governments and companies can be obtained for free, helping those who have research questions to answer. These two changes are shaping statistical learning in developing countries, making the available tools for developed and developing countries less unequal. In this chapter, we will show how statistical educators can take advantage of some of these resources, making their students more prepared for the changes that are already happening in the statistical world in the 21st century